Lack of Association Between Polymorphisms in TXNRD2 and LMX1B and Primary Open-Angle Glaucoma in a Saudi Cohort - Kondkar, Altaf A.; Azad, Taif A.; Alobaidan, Abdullah S.; Sultan, Tahira; Osman, Essam A.; Almobarak, Faisal A.; Lobo, Glenn P.; Al-Obeidan, Saleh A. (Frontiers in Genetics, 2021)
Objective: Recent studies have demonstrated an association of single nucleotide polymorphisms (SNPs) rs35934224 in TXNRD2 and rs6478746 near LMX1B genes in primary open-angle glaucoma (POAG) among Europeans. We performed a retrospective, case-control study to investigate the association between the rs35934224 (TXNRD2) and rs6478746 (LMX1B) and POAG in a middle-eastern population from Saudi Arabia. Methods: DNA from 399 participants consisting of 150 POAG cases (83 males and 67 females) and 249 controls (135 males and 114 females) were genotyped using TaqMan® real-time PCR. Statistical tests were performed to evaluate genetic association with POAG and related clinical indices. Results: The minor allele frequency (MAF) of rs35934224[T] was 0.19 and 0.20 in POAG and controls, respectively. The difference was non-significant (odds ratio [OR]=1.08, 95% confidence interval [CI]=0.75-1.55, p=0.663). Likewise, rs6478746[G] MAF was 0.12 in both cases and controls with no statistical significance (OR=1.02, 95%CI=0.67-1.56, p=0.910). Genotype analysis showed no association with POAG for both the SNPs in combined and gender-stratified groups. Regression analysis showed no significant effect of risk factors such as age, sex, rs35934224, and rs6478746 genotypes on POAG outcome. Furthermore, both the SNPs showed no significant genotype effect on clinical indices such as intraocular pressure (IOP) and cup/disc ratio in POAG patients. Conclusions: Rs35934224 in TXNRD2 and rs6478746 near LMX1B genes are not associated with POAG or related clinical indices such as IOP and cup/disc ratio in a Saudi cohort. Since the study is limited by sample size further investigations are needed to confirm these results in a larger cohort.